Terminal deletion (14)(q32.3): a new case. - Telford, N (1990)
A mildly dysmorphic, 2 year old girl with mental retardation was found to have a small de novo terminal deletion of the long arm of chromosome 14, del(14)(q32.3). She was found to have features in common with two previous terminal deletion cases and particularly with the well documented ring 14 syndrome, although seizures, a characteristic feature of ring 14, were notably absent.